PENGARUH PENGAWASAN TERHADAP DISIPLIN KERJA PEGAWAI SEKRETARIAT DAERAH KABUPATEN HALMAHERA UTARA - KABIAY, OSNAVITA; POSUMAH, JOHNNY HANNY; KOLONDAM, HELLY FEBRINA (JURNAL ADMINISTRASI PUBLIK, 2017)
Summary : This study aims to determine and analyze the influence of supervision on the discipline of employeesof the Regional Secretariat of North Halmahera Regency. Research Methods that the authors use in this studyis a quantitative research method. Data and information collected through questionnaire technique andcompleted with interview technique, data source / respondent of research is all secretariat officer of northHalmahera regency area as much 80 people. Analytical techniques used by hypothesis testing are frequencytables, product moment correlation and simple linear regression. Based on the description of the data it turns outmost of the respondents are giving an assessment of the surveillance are in the variables category of "high".Then as many as 22 respondents or 27.5% other employees who stated that the supervision at the Secretariat ofthe District of North Halmahera is in the category of "medium" while the category "low" does not exist, whileemployee discipline at the Secretariat of the District of North Halmahera is in the category "high ", 2 employeesor 2.5 respondents stated that the work discipline of the North Halmahera District Secretariat is in the" moderate"category, while the" low "category does not exist. Thus, it can be concluded that between the supervision withthe discipline of employees of the Secretariat of North Halmahera Regency at a very convincing level of trust.Keywords: Supervision, work discipline of employees